2015
DOI: 10.1002/cad.20117
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity and Psychological Well-Being of International Transracial Adoptees: A Curvilinear Relationship

Abstract: Research in general has shown a beneficial effect of ethnic identity on adoptees' psychological well-being. However, studies also indicate that overemphasis on birth culture and racial/ethnic differences may negatively impact adoptees' overall adjustment. Using Rojewski's () and Brodzinsky's () propositions of a balanced approach to adoption and culture issues, this study examines the curvilinear relationship between ethnic identity and psychological well-being of international adoptees (i.e., psychological we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Although a heightened ethnic identity may be a protective factor for nonadopted Chinese Americans coping with COVID-19-related racism (Litam & Oh, 2020), this may not be applicable to transracial adoptees. Mohanty (2015) found that overemphasis on one’s ethnic identity, birth culture, and racial and ethnic differences can negatively influence transnational, transracial adoptees’ psychological well-being. This may contextualize our participants’ desire to dissociate from China and Chinese people.…”
Section: Discussionmentioning
confidence: 99%
“…Although a heightened ethnic identity may be a protective factor for nonadopted Chinese Americans coping with COVID-19-related racism (Litam & Oh, 2020), this may not be applicable to transracial adoptees. Mohanty (2015) found that overemphasis on one’s ethnic identity, birth culture, and racial and ethnic differences can negatively influence transnational, transracial adoptees’ psychological well-being. This may contextualize our participants’ desire to dissociate from China and Chinese people.…”
Section: Discussionmentioning
confidence: 99%
“…One study of transracially adopted children found greater adjustment difficulties in children who internalised the perceived dominant skin colour of the host country as more desirable (Juffer and van IJzendoorn). Mohanty's (2015) study found a curvilinear relationship between adoptees' sense of ethnic identity and self-esteem, in that a moderate level of identification with ethnicity of origin is associated with positive esteem whereas low and high levels are related to low selfesteem. However, Le Mare and Audet found that exposure to culture of origin did not relate to behavioural problems.…”
Section: Contextual Factorsmentioning
confidence: 79%
“…Consequently, parents may not know how best to support their children after they have experienced a transracial adoption microaggression (Barn, 2013; Dolan, 2015). For instance, transracial adoptees may be the subject of microaggressions from people of their birth country’s racial or ethnic group who criticize them for “acting too White” or not being “real Asians” and may also be singled out by White individuals, including the members of their extended adoptive family, for “acting too Asian” (Baden, 2008; Mohanty, 2015; Wing, 2019). These experiences can be difficult to cope with, especially for youth who may not have the psychological and social resources or capacity to understand, process, and seek the support they need in these instances (Chang et al, 2017).…”
Section: Case Analysismentioning
confidence: 99%